Enhancing Pediatric Forearm Fracture Management: The Role of Extension Casting in Reducing Repeat Interventions (Journal of Rangpur Medical College, 2024)
Background: Fractures of the forearm are common in the pediatric population, often requiring careful management to ensure optimal outcomes and minimize long-term complications. Among the various treatment modalities available, extension casting has emerged as a promising approach in pediatric forearm fracture management. Objective: The aim was to evaluate the effectiveness of extension casting in reducing the need for repeat interventions in pediatric forearm fractures. Methods: This study was a prospective cohort study conducted at the Department of Orthopaedics & Traumatology of Khwaja Yunus Ali Medical College & Hospital, Enayetpur, Sirajganj, from July 2020 to July 2023. A total of 60 pediatric patients, aged 5-12 years, with acute forearm fractures were enrolled. Different statistical methods were adopted in this study. All analyses were performed using SPSS version 25.0. Results: The study of 60 pediatric patients with forearm fractures showed a mean age of 8.2 years, with 60% males. Most fractures were in the middle third of the forearm (60%). At 12 weeks, 87% maintained satisfactory reduction. Only 10% required repeat interventions. PODCI scores indicated excellent functional recovery, low residual pain, and high satisfaction. Minor complications included skin irritation (6.7%) and transient nerve palsy (3.3%), with no long-term complications. Conclusion: The results of this study affirm the effectiveness and safety of extension casting in managing pediatric forearm fractures. This method not only ensures better maintenance of fracture reduction and reduces the need for repeat interventions but also yields excellent functional outcomes and low complication rates.J Rang Med Col. September 2024; Vol. 9, No. 2: 50-55